2020
DOI: 10.1111/are.15004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of taurine or sodium diformate supplementation to a low fishmeal plant‐based diet fed to European sea bass ( Dicentrarchus labrax )

Abstract: The effects of either taurine (T) or sodium diformate (NDF) supplementation to a low fishmeal (FM) plant‐based diet on growth, health status, immunity and muscle cellularity of European sea bass, Dicentrarchus labrax, were investigated. Four isoproteic (44% CP) and isolipidic (17% L) diets were produced to contain 46% FM as a control diet, or 20% FM and a mixture of plant nutrients (PMX). The plant‐mix diets were either supplemented or not with 1% T or 0.3% NDF. Each diet was fed to triplicate groups of seabas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 54 publications
(116 reference statements)
0
4
0
Order By: Relevance
“…Adding crystalline amino acids (CAAs) to plant-ingredients-based diets is likely to become an increasingly common practice to optimize the nutritional value of these diets. It has been found that crystalline amino acid supplementation improved fish growth and protein synthesis, as well as immunity and antioxidant capacity [ 6 , 7 ]. Methionine is a major limiting EAA in most plant-based ingredients of fish feed [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adding crystalline amino acids (CAAs) to plant-ingredients-based diets is likely to become an increasingly common practice to optimize the nutritional value of these diets. It has been found that crystalline amino acid supplementation improved fish growth and protein synthesis, as well as immunity and antioxidant capacity [ 6 , 7 ]. Methionine is a major limiting EAA in most plant-based ingredients of fish feed [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…The growth and feed intake of European seabass were also further repressed by plant oil if FM content was high. However, replacing FM and fish oil at the same time does not necessarily result in bad growth, 381–383 and the impact of low FM could be significantly improved by bioactive feed additives 384–386 . Thus, future studies should aim more at the overall reduction of oceanic products in fish diets rather than only replacing fish oil when the FM content is still very high.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the study of El-Sayed Ali et al (2018) showed an increased number of lymphocytes and monocytes in the blood and alteration in the liver and kidney structure (10 and 20 g/kg) when sodium butyrate was included in the diet of Nile tilapia. Many studies have been conducted on immune responses of European seabass (Dicentrarchus labrax) supplemented with different SCFA salts, such as sodium butyrate, sodium propionate, sodium diformate, and potassium diformate (Wassef et al, 2017(Wassef et al, , 2020(Wassef et al, , 2021(Wassef et al, , 2023Abdel-Mohsen et al, 2018). Notably, Abdel-Mohsen et al (2018) reported that microencapsulated sodium butyrate at a rate of 2 or 3 g/kg increased the serum immunoglobulins, respiratory burst, phagocytosis, myeloperoxidase, lysozyme, and bactericidal activity in D. labrax fry (individual body weight, IBW of 0.45 g).…”
Section: Immunomodulatory Effects Of Scfas and Its Role In Disease Re...mentioning
confidence: 99%
“…In D. labrax (IBW of 4.75±0.04 g), it has been found that dietary sodium diformate at a dosage of 3 g/kg improved the health status by increasing the leucocyte count, serum proteins, monocyte and lymphocyte percentages, lysozyme activity, and leucocytes phagocytosis (Wassef et al, 2017). Similarly, Wassef et al (2021) conducted a study on the effect of supplementary sodium diformate in the low fish meal plant-based diet on D. labrax (IBW of 13.71 g) in which they have found that the supplementation of sodium diformate (3 g/kg) with the plantmix diet increased the major blood constituents and serum immunity indicators.…”
Section: Immunomodulatory Effects Of Scfas and Its Role In Disease Re...mentioning
confidence: 99%